Is Horizontal Mattress Suturing More Effective Than Simple Interrupted Suturing on Postoperative Complications and Primary Wound Healing After Impacted Mandibular Third Molar Surgery? - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2017)
The aim of this clinical study was to compare the influence of 2 different suturing techniques on postoperative complications and wound healing after surgical extractions of impacted mandibular third molars. In this randomized split mouth study, 30 patients were examined in whom 60 consecutive surgical extractions of symmetrically positioned impacted mandibular third molars were performed. After the extractions, the surgical flaps were sutured with either the simple interrupted or horizontal mattress suturing technique. Postoperative swelling and trismus were recorded on the 2nd, 7th, and 10th days. Pain was recorded in a 7-day diary and wound dehiscence was recorded on the 10th postoperative day. Statistical evaluation of data was made using Mann-Whitney U test and Pearson correlation. There were no statistical differences between the 2 suturing techniques in terms of postoperative pain, trismus, and swelling (P> 0.05). There was significantly less wound dehiscence in the horizontal mattress suturing group than in the simple interrupted suturing group (P: 0017). According to the results of this study, the horizontal mattress suturing technique is more effective than the simple interrupted suturing technique on wound healing after impacted mandibular third molar surgery, although it does not decrease the levels of pain, trismus, and swelling.
Keywords: Horizontal mattress suturing; impacted third molar; primary wound healing; simple interrupted suturing; INFLAMMATORY COMPLICATIONS; FLAP DESIGN; 2ND MOLARS; PAIN; TRISMUS; CLOSURE; EXTRACTION; REMOVAL; HEALTH; OZONE